Parental knowledge, attitude and practice of allergy disease in Selangor - Tengku Azhar, Tengku Norbaya; Che Hassan, Muhammad Rahimi; Mohd. Zazi, Norhafizah; Abd Wahab, Noor Akmal; , Saiyidatul Nadiah; Ishak, Nur Syakireed; Abdul Ghani, Radiah (2019)
Allergy prevalence becoming a worrisome issues amongst society. It’s not just discussed as worldwide issue but also effect sufferer even in a small institution such as the family. Corresponded to the family as the simplest unit of society, parental knowledge, attitude and practice play a crucial roles in allergy prevalence, prevention and treatment strategy. Allergy known to cause social and economic burden of the sufferer as well as to the closer family member. In Malaysia, the misconception of certain allergy symptom and misused of self- perceive method for allergy diagnosis becoming another real challenges. This scenario could lead to improper clinical diagnosis thus effect the treatment accuracy and upturn the cost of the treatment. This paper highlighted the differences between paternal and maternal knowledge, attitude and practice towards allergy reaction. This study also summarized the important of having adequate knowledge self-perceiving the allergy disease as this method is useful to give surface overview on allergy prevalence. This cross-sectional study involved 117 pair of parents in Selangor with the age ranged from 18-50 years old. A self-administered questionnaire has been used to by self-perceive method to indicate respondent’s allergy status and their knowledge and practice towards allergy disease. As overall, the common symptoms of allergy among parents were allergy rhinitis, eczema and dry ant itchy rashes at skin with percentage ranged from 6.8% to 28.4% of occurrence. The data also indicated that n=17 (14.4%) of mothers and n=8 (6.8%) of fathers allergy to seafood while n=11 (9.3%) of mothers and n=15(12.7%) of fathers also allergy to house dust mites. Pearson correlation between knowledge of allergy term, cause and symptom with allergy prevention and treatment shows significant correlation with (r = 0.244, P<0.001) for maternal and (r = 0.262, P<0.001) for paternal respectively. This outcome indicated that, the decision on treatment strategy among parents strictly depends on their level of knowledge about allergy. Other test such as Chi Square Test among parents also determined the treatment strategy based on consultation of allergy symptom with an expert of health personnel. It shows that n=14 (42.5%) of mothers with allergy and n=23 (65.7%) of fathers with allergies do not consult to an expert regarding their allergy prevalence and symptom. It also shows significant association for both with (P<0.001). Parental knowledge in society represent their involvement in prevention and treatment strategy for allergy sufferer especially the offspring. Adequate knowledge and awareness at this unit of society compromised a better future to control its prevalence.